2010
DOI: 10.1007/s00134-010-2057-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of norepinephrine on renal perfusion, filtration and oxygenation in vasodilatory shock and acute kidney injury

Abstract: Restoration of MAP from 60 to 75 mmHg improves renal oxygen delivery, GFR and the renal oxygen supply/demand relationship in post-cardiac surgery patients with vasodilatory shock and AKI. This pressure-dependent renal perfusion, filtration and oxygenation at levels of MAP below 75 mmHg reflect a more or less exhausted renal autoregulatory reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(96 citation statements)
references
References 39 publications
3
91
0
2
Order By: Relevance
“…On the other hand, too low a dose of norepinephrine may result in an arterial blood pressure that may be below the limit of renal autoregulation, i. e., when renal blood fl ow becomes pressure-dependent. In a recent study in post-cardiac surgery patients with norpinephrine-dependent vasoplegia and concomitant AKI, the eff ects of norepinephrine on renal perfusion, fi ltration and oxygenation were evaluated [47]. Nor epineph rine infusion rate was randomly and sequentially titrated to target a mean arterial pressures (MAP) of 60, 75 and 90 mm Hg.…”
Section: Vasodilatory Shock and Aki: Role Of Norepinephrinementioning
confidence: 99%
“…On the other hand, too low a dose of norepinephrine may result in an arterial blood pressure that may be below the limit of renal autoregulation, i. e., when renal blood fl ow becomes pressure-dependent. In a recent study in post-cardiac surgery patients with norpinephrine-dependent vasoplegia and concomitant AKI, the eff ects of norepinephrine on renal perfusion, fi ltration and oxygenation were evaluated [47]. Nor epineph rine infusion rate was randomly and sequentially titrated to target a mean arterial pressures (MAP) of 60, 75 and 90 mm Hg.…”
Section: Vasodilatory Shock and Aki: Role Of Norepinephrinementioning
confidence: 99%
“…The major cause for the emergence of acute kidney injury after cardiac surgery is surely ischemia secondary to renal hypoperfusion. (26) Scientific research shows that a higher time of mechanical ventilation significantly exposes patients to the occurrence of acute kidney injury after cardiac surgery. (19) In this study, despite the high incidence of acute kidney injury, the invasive ventilation strategy employed an average positive end-expiratory pressure of 5.4±0.9cmH 2 O.…”
Section: Discussionmentioning
confidence: 99%
“…Renal blood fl ow calculation is based on measured changes in te mper ature of the renal vein blood after injection of a bolus of isotonic saline at room temperature [19]. Using such methods, Ricksten et al have conducted several elegant studies of global renal perfusion in cardiac surgery patients [20][21][22]. For example, they demonstrated that restoring mean arterial pressure (MAP) from 60 to 75 mm Hg improved the renal oxygen supply/demand relationship after cardiac surgery in patients with vasodilatory shock and AKI [21].…”
Section: Renal Vein T Hermodilution Methodsmentioning
confidence: 99%
“…Using such methods, Ricksten et al have conducted several elegant studies of global renal perfusion in cardiac surgery patients [20][21][22]. For example, they demonstrated that restoring mean arterial pressure (MAP) from 60 to 75 mm Hg improved the renal oxygen supply/demand relationship after cardiac surgery in patients with vasodilatory shock and AKI [21]. Th is technique, however, remains highly invasive and, because of the risk of renal vein thrombosis, can only be applied for a limited period of time.…”
Section: Renal Vein T Hermodilution Methodsmentioning
confidence: 99%